2020
DOI: 10.3892/or.2020.7682
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑16‑5p regulates cell survival, cell cycle and apoptosis by targeting AKT3 in prostate cancer cells

Abstract: Prostate cancer (PCa) is a malignancy with the highest morbidity rate in 105 countries worldwide and was a major cause of cancer-associated death in men in 2018. Accumulating evidence suggests that microRNAs (miRNAs/miRs) have important functions in the carcinogenesis of PCa, and may provide novel treatment targets. Previous studies have indicated that miR-16-5p is associated with PCa. However, the relevance and importance of miR-16-5p in PCa carcinogenesis are still not completely understood. In the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Studies have pointed out that upregulating the expression of miR-16-5p can inhibit the proliferation and metastasis of liver cancer cells [ 12 ]. miR-16-5p inhibits the survival of prostate cancer cells by targeting protein kinase 3 (AKT3), regulates cell cycle distribution, and induces apoptosis [ 13 ]. In addition, miR-16-5p also mediates the inhibitory effect of knockdown Linc0021 on the biological behavior of nonsmall cell lung cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have pointed out that upregulating the expression of miR-16-5p can inhibit the proliferation and metastasis of liver cancer cells [ 12 ]. miR-16-5p inhibits the survival of prostate cancer cells by targeting protein kinase 3 (AKT3), regulates cell cycle distribution, and induces apoptosis [ 13 ]. In addition, miR-16-5p also mediates the inhibitory effect of knockdown Linc0021 on the biological behavior of nonsmall cell lung cancer [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miR 221 and miR 222 act on different kinase-dependent cyclin inhibitors such as p27 kip1 in nasopharyngeal carcinomas, which causes the hyperactivation of cyclins with increased tumor growth [ 44 ]. Similarly, other works have demonstrated that miR-16, a product downregulated in prostate cancer cells, can directly target AKT3, thus ameliorating cell cycle dysregulation and inducing cell apoptosis [ 45 ]. According to recent reviews on penile cancer [ 46 ], an overexpression of oncogenic miRNAs (miR-223-3p, miR-107 and miR-21-5p) was directly involved in PTEN suppression in addition to alterations in the mitogen-activated protein kinase pathway MAPK (ERK1/ERK2), whereas miR-145 downregulation drove to marked alterations in oncogenic genes such as c-myc.…”
Section: Role Of Micrornas In Cell Cyclementioning
confidence: 95%
“…Through bioinformatic analyses, these authors predicted its interaction with targets such as WEE1, Chk1, and CDC27 ( 66 ). miR-16-5p had been previously observed to inhibit proliferation in prostate ( 106 ) and breast ( 107 ) cancers by targeting AKT.…”
Section: Ncrnas Involved In Cell Cyclementioning
confidence: 99%